2022
DOI: 10.3390/ijms23179522
|View full text |Cite
|
Sign up to set email alerts
|

LjAMT2;2 Promotes Ammonium Nitrogen Transport during Arbuscular Mycorrhizal Fungi Symbiosis in Lotus japonicus

Abstract: Arbuscular mycorrhizal fungi (AMF) are important symbiotic microorganisms in soil that engage in symbiotic relationships with legumes, resulting in mycorrhizal symbiosis. Establishment of strong symbiotic relationships between AMF and legumes promotes the absorption of nitrogen by plants. Ammonium nitrogen can be directly utilised by plants following ammonium transport, but there are few reports on ammonium transporters (AMTs) promoting ammonium nitrogen transport during AM symbiosis. Lotus japonicus is a typi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
(42 reference statements)
0
7
0
Order By: Relevance
“…This expands the range of root absorption and promotes the ability of the roots to absorb nitrogen directly. In addition, AMF hyphae absorbed more NO 3 - -N than NH 4 + -N, which is inconsistent with the results of previous studies showing that AMF prefer NH 4 + -N (Li et al ., 2013; Wang et al ., 2022). This may be related to the N preference of cotton in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…This expands the range of root absorption and promotes the ability of the roots to absorb nitrogen directly. In addition, AMF hyphae absorbed more NO 3 - -N than NH 4 + -N, which is inconsistent with the results of previous studies showing that AMF prefer NH 4 + -N (Li et al ., 2013; Wang et al ., 2022). This may be related to the N preference of cotton in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the phylogenetic relationships of AMT2 proteins in different plant species, the sequences of AMT2 proteins from A. thaliana (Gazzarrini et al, 1999), rice (Oryza sativa) (Sonoda et al, 2003), soybean (Glycine max) (Kobae et al, 2010), maize (Zea mays) (Hui et al, 2022), and Lotus japonicus (Wang et al, 2022) were obtained from the previous study, and the sequences from Ricinus communis, belonging to Euphorbiaceae, were identified using the identification method for the cassava AMT2 gene family. Multiple sequence alignment using MUSCLE and default parameters was applied to evaluate the evolutionary relationship of MeAMT2s proteins in cassava (Edgar, 2004), and a neighbor-joining (NJ) phylogenetic tree was established based on the alignment utilizing the MEGA version X software (Kumar et al, 2018) with 1000 bootstrap replications.…”
Section: Analysis Of Phylogenetic Conserved Motifs and Gene Structurementioning
confidence: 99%
“…GmAMT4.1 showed specific expression in arbusculated cortical cells and localized on the periarbuscular membrane (Kobae et al, 2010). The LjAMT2.2 gene was significantly upregulated when inoculating with arbuscular mycorrhizal fungi (AMF) (Wang et al, 2022). Phylogenetic relationship analysis showed that MeAMT2.2, MeAMT2.4, MeAMT2.7, GmAMT4.1, and LjAMT2.2 were all assigned to subgroup 3 (Figure 2).…”
mentioning
confidence: 99%
“…Z m T u b u l i n (Zm00001d009780) and ZmGAPDH (Zm00001d049641) were used as the endogenous reference genes to standardize the relative expression levels of ZmGRF genes. Our previous published work provided extensive knowledge regarding qRT-PCR reactions (Wang et al, 2022). The 10 -(DCt/3) method was used to determine the relative gene expression levels (Li et al, 2005;Liao et al, 2014).…”
Section: Plant Materials Growth Conditions and Treatmentsmentioning
confidence: 99%